STRATEGI DAKWAH KEPADA KELUARGA: (Studi Pemikiran Tokoh Dakwah Ustadz Khalid Basalamah) - Angger Bimantara; Luluk Fikri Zuhriyah (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2022)
This study aims to explain the da’wah strategy to the family in Ustaz Khalid Basalamah’s perspective. Especially da’wah strategy used by the husband to appeal to his wife and vice versa from the wife to the husband. This study is conducted as a qualitative research with a character study approach as to be able to understand a character point of view. This study reveals Ustaz Khalid Basalamah’s perpectives in da’wah strategy of a husband towards the wife is a sentimental strategy (al manhaj al a’thifi) and that of the wife towards the husband is a rational strategy (al manhaj al aqliy). Ustaz Khalid Basalamah stated three types of sentimental strategy (al manhaj al a’thifi) that a husband could use towards his wife which are: da’wah with an embrace, da’wah with love, and da’wah with firmness. He also stated two types of rational strategy (al manhaj al aqly) that a wife could use towards the husband, they are: da’wah with questions and da’wah by telling stories.